Energy Production, Load and Battery Management Framework with Supporting Methods for Smart Microgrids - Catthoor, Francky; Taniguchi, Ittetsu; Georgilakis, Pavlos S.; Zhao, Dafang; Soudris, Dimitrios; Siozios, Kostas; Kazantzidis, Andreas; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book provides an overview of the results of a large university collaboration addressing the emerging topic of distributed, localized energy grids and also smart grids. The authors discuss promising, consolidated results from their consortium research activities from the past decade. The methods described achieve unprecedented accuracy levels within reasonable run-times, compatible with on-line monitoring and forecasting as needed for smart grids. Discusses physics-based, short-term wind turbine and PV Eyield forecasting techniques,, which enable unprecedented accuracy; Describes a multi-time-scale energy management framework, combining renewable production, HVAC loads and battery storage; Enables up-scalable approach to aggregated HVAC load modelling and forecasting.
Chapter 1. Motivation, Focus and Contributions of this Book -- Chapter 2. Accurate PV Energy Yield Forecasting -- Chapter 3. Accurate Energy Yield Forecasting for Wind Turbine Parks -- Chapter 4. Online HVAC control for Energy Efficiency and Thermal Comfort -- Chapter 5. Multi-Timescale Energy Management Framework.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Embedded computer systems; Cooperating objects (Computer systems).; Electric power distribution; Embedded Systems; Cyber-Physical Systems; Energy Grids and Networks